Safe drinking water for rural communities using a low-cost household system. Effects of water matrix and field testing. (December 2021) - Pichel, N.; Lubarsky, H.; Afkhami, A.; Baldasso, V.; Botero, L.; Salazar, J.; Hincapie, M.; Byrne, J.A.; Fernandez-Ibañez, P.
Abstract: The relationship between turbidity (T) and ultraviolet C (UVC) disinfection is still not clearly understood, as well as no attention has been paid to the contribution of natural organic matter (NOM). The present work assessed the influence of particulate and NOM on the UVC disinfection efficiency in terms of E. coli and MS2 removal at bench collimated beam (CB) and flow-UVC systems, both in the laboratory and in the field (Colombia). The flow-UVC reactor was installed as part of a household water treatment (HWT) system consisting of filtration + UVC disinfection. Tests were performed according to the WHO standards using fine test dust, humic acid (HA), and MS2 and E. coli as microbiological indicators. CB results showed a significant decrease in the inactivation rate of MS2 in the presence of small concentrations of HA (3.5 mg/L), with killing dose increasing a 65%, vs. non-significant effects of turbidity in the range of 0–20 NTU. Following the same trend, in flow-UVC tests the inactivation efficiency of MS2 decreased solely in the presence of HA. At the same HA concentration and flow rate, an increase in turbidity of 17.6 NTU showed a negligible effect. Conversely, in the presence of HA, UVT254 dropped from 88.7% (0 mg/L HA) to 73.3%, reducing MS2 inactivation by 1–2 log-units. Finally, the HWT system could be classified as protective working at flow rates ≤5 L/min. However, in the presence of 3.5 mg/L HA (UVT254 < 75%), it presented a limited protection for viruses. Highlights: Study of the effects of turbidity and NOM on E. coli and MS2 UVC inactivation. Strong detrimental effect of HA (0–3.5 mg/L) on UVT254 reducing MS2 inactivation by 1–2 log-units. Non-significant effect of turbidity (0–20 NTU) on UVC disinfection efficiency. SAFEWATER HWT system classified as protective following the WHO standards.